Mobilization of domestic capital : report and documents of the second working party of experts - United Nations (Bangkok : Dept. of Economic Affairs, ECAFE., 1953)
The book is divided into two parts. Part I. Report of the Second Working Party of Experts on Mobilization of Domestic Capital. Part II. Summaries of Papers Submitted to the Working Party.
Issued with the United Nations publications sales numbers.
rpm 09/11/2017
Loans
Keywords: Investments; Banks and banking; Asia